BO‘LAJAK BOSHLANG‘ICH SINF O‘QITUVCHILARINING RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH KOMPETENTLIGINI SHAKLLANTIRISH DARAJALARI TAHLILI - Ergasheva, F.T. (SCIENCE and SOCIETY, 2023)
The article describes the levels of formation of digital competence on the example of future primary school teachers. The levels are presented in a meaningful way, and didactic methods for assessing the formation of each level of digital competence are proposed. Digital competence is acquired in a personal-subjective way, as it is the result of the student’s self-development, the synthesis of his activities and personal experience. As a result, it is proposed to design a student’s personal learning environment as a condition for the development of digital competence in higher educational institutions.
Keywords: digital technology; digital competence; competence; levels of digital competency